Unrequited Love in Billie Eilish™s Selected Songs: Imagery and Biographical Approach - Namira, Zuhra; Setiasari, Winda (TRANSFORM: Journal of English Language Teaching and Learning, 2022)
The focus of this study was to analyze the types of imagery that represented unrequited love in the five selected song lyrics based on Billie Eilish™s life background. The five selected songs were œWish you were gay, œ8, œHostage, œMy boy, and œYour Power. This study applied the theory imagery of Perrine™s theory and Kennedy and Gioia™s biographical approach. The qualitative content analysis was employed as the method in this study. The data were the five selected song lyrics and the life background of Billie Eilish. The source of data taken from transcript lyrics and the interviews also documentary of Billie Eilish. The researcher found there were five types of imagery found in the song lyrics. They were visual imagery (15), auditory imagery (2), tactile imagery (1), kinesthetic imagery (7), and organic imagery (8). Billie Eilish experienced three categories of unrequited love: crush on someone who is unavailable, pursuing the love object, and unequal love relationship portrayed in the five selected songs. Billie Eilish™s life background greatly influenced her song lyrics, starting with her depression and suicidal thought, her unique fashion style, and herself as a drug-free teenager.